FACTORS ASSOCIATED WITH SEASONAL INFLUENZA IMMUNIZATION IN PEOPLE WITH CHRONIC ILLNESSES: Immunization in chronic illness - Gazibara, Tatjana; Arsenović, Sladjana (Medicinski podmladak, 2021)
At a global level, 3 to 5 million people annully present severe clinical forms of influenza and up to 650,000 people die of influneza-related complications. People with chronic illnesses, such as cardiovascular, pulmonary, renal, hepatic, neurologic, hematologic and metabolic diseases or those reciveing immunosuppressive therapy, constitute a high-risk population group for the development of influenza-related complications, more severe clinical course and poorer health-related outcomes. Because of this, people with chronic illnesses are of high priority to receive the influenza vaccine. Immunization represents the key strategy to prevent influenza both in terms of effectiveness and health care costs. Based on the World Health Organization (WHO) recommendations, adequate influenza immunization coverage among people with chronic illnesses is set at 75%. However, few countries achieve this threshold. Understanding predictive factors of vaccination, at different levels of health care delivery (such as individuals, service providers, health policy), is essential to secure acceptance of influenza immunization and achieve the recommended level of vaccination coverage. In this mini review, we summarized the available evidence regarding influenza vaccination coverage and factors associated with vaccine uptake in people with chronic diseases as a whole, as well as according to specific illnesses such as: cardiovascular and pulmonary disorders, diabetes and cancer. Based on the reviewed empirical evidence, we found a wide spectrum of factors associated with immunization against influneza in people who have chronic illnesses. Although diverse, these factors can be systematized into 4 distinctive groups: socio-demographic characteristics, individual attitudes and beliefs, health promoting behaviors and factors related to the health care system. Further efforts are needed to improve the influenza vaccination coverage. The immunization strategy needs to include the health care system and the community to support people with chronic illnesses to continously accept the influenza vaccine.